Perfluoropolymer tubular membrane and preparation method thereof

Through the preparation method of perfluoropolymer tube film, the problem of low oil-water separation efficiency under medium and high temperature conditions of industrial waste oil treatment is solved, and an efficient and environmentally friendly oil-water separation effect is achieved.

CN119896973APending Publication Date: 2025-04-29SHANGHAI UNIV OF ENG SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411223113.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing industrial waste oil treatment processes have problems such as environmental protection, efficiency and high temperature resistance, especially the application of tubular membranes under high temperature conditions.

Method used

The perfluoropolymer tube film and its preparation method are adopted to prepare a high-temperature, porous, and high-throughput perfluoropolymer tube film through the configuration of the cast film liquid, the preparation and sintering process of primary film.

Benefits of technology

It realizes efficient oil-water separation under high temperature conditions, improves the hydrophobicity, oil flux and service life of the membrane, and is simple and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119896973A_ABST
    Figure CN119896973A_ABST
Patent Text Reader

Abstract

The invention discloses a perfluoropolymer tubular membrane and a preparation method thereof, and the preparation method comprises the following steps: dispersing a liquid containing a perfluoropolymer and a pore-foaming agent in water to obtain a membrane casting stock solution; dispersing inorganic particles in the casting membrane stock solution to obtain a casting membrane solution; flatly laying the stainless steel mesh on an automatic film coating machine, forming a perfluoropolymer film layer on the inner surface of the stainless steel mesh through constant-speed operation of a film scraping device, drying so as to preliminarily solidify a film casting solution in hot air, and combining an ultrasonic welding technology to obtain a primary perfluoropolymer tubular film; and sintering the primary perfluoropolymer tubular membrane, and naturally cooling to obtain the perfluoropolymer tubular membrane. The perfluoropolymer tubular membrane prepared by the invention not only is resistant to high temperature, but also has the characteristics of porosity and high flux, and the hydrophobicity, the oil flux, the service life and the anti-pollution capacity of the tubular membrane are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of membrane materials, and in particular to a perfluoropolymer tubular membrane and a preparation method thereof. Background Art

[0002] Industrial waste oil is a common environmental pollutant. Every year, 200 to 300 million tons of industrial waste oil endanger human health and aquatic resources. The total amount of deteriorated substances and impurities in waste oil is usually within the range of 1%-2%, and the rest is still good ingredients. As long as it is carefully treated, the quality can fully meet the new oil standard, thereby realizing the sustainable development of oil resources and the protection of the ecological environment. At present, there are many disadvantages in the common waste oil treatment processes in the market. For example, the early sulfuric acid bleaching clay method mainly focuses on distillation-pickling-bleaching clay refining process. The quality of the regenerated oil is not high, it has a rancid smell, and can only be used as a low-grade oil product, and it will form waste acid residues and waste bleaching clay and wastewater. Secondary pollution; the subsequent solvent extraction method is mainly based on distillation-furfural refining-bleaching clay refining. The quality of the regenerated oil obtained by this process is improved, but a large amount of organic solvents are used in the process, which are slightly toxic and will cause secondary pollution. In addition, the temperature resistance is limited, the recovery cost is high, and the recovery is difficult. The KTI process commonly used in Western developed countries has high temperature and high pressure requirements, requires hydrogen supply, and must have high safety standards, high operating costs, and harsh operating conditions. Therefore, there is an increasing demand for environmentally friendly, efficient, and high-temperature resistant waste oil treatment processes.

[0003] The application of membrane separation technology in waste oil treatment processes is becoming more mature. The treatment facilities supporting this technology are relatively simple, relatively easy to operate effectively, and have good separation efficiency. The treatment environment of industrial waste oil usually requires high temperature conditions, but there are few reports on tubular membranes in related applications.

[0004] The treatment and reuse of industrial waste oil is an effective way to achieve resource optimization, which can not only protect the ecological environment, but also generate certain economic benefits. Therefore, the development of a high temperature resistant perfluoropolymer tubular membrane and its preparation method has excellent application prospects. Summary of the invention

[0005] In view of the problem of treatment and recycling of industrial waste oil, the present invention provides a method for preparing a perfluoropolymer tubular membrane which is resistant to high temperature, has a simple preparation process and is environmentally friendly.

[0006] To this end, the present invention adopts the following technical solutions:

[0007] A method for preparing a perfluoropolymer tubular membrane comprises the following steps:

[0008] S1, preparation of casting solution: dispersing a liquid containing a perfluoropolymer and a porogen in deionized water, heating and stirring at 60-90°C for 2-5 hours to obtain a casting stock solution; keeping the stirring conditions unchanged, weighing inorganic particles and dispersing them in the casting stock solution, continuing to stir for 2-5 hours, and then vacuum degassing for 2-4 hours, and finally ultrasonically treating for 30-40 minutes to obtain a uniform casting solution (suspension), in which the solid content of the porogen is 4-10wt%, the solid content of the inorganic particles is 1-3wt%, and the solid content of the perfluoropolymer is 15wt%;

[0009] S2, preparation of nascent perfluoropolymer tubular membrane: a stainless steel mesh is laid flat on an automatic coating machine, 8-15 ml of casting liquid is placed on one end of the stainless steel mesh, and a film scraper is uniformly advanced at a speed of 35-45 mm / s to obtain a perfluoropolymer film layer uniformly coated on the inner surface of the stainless steel mesh, followed by drying at 60-90° C. for 1-2 min to allow the casting liquid to initially solidify in hot air, and finally ultrasonically welded in an ultrasonic welding machine to obtain a nascent perfluoropolymer tubular membrane;

[0010] S3, preparation of perfluoropolymer tubular membrane: placing the primary perfluoropolymer tubular membrane obtained in step S2 into a muffle furnace, gradually heating to 300-350° C. and sintering at 300-350° C. for 5-10 min, and obtaining a perfluoropolymer tubular membrane after natural cooling.

[0011] Preferably, the perfluoropolymer in step S1 is one of polyperfluoroethylene propylene (FEP), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and poly(tetrafluoroethylene perfluoroalkoxy vinyl ether) copolymer (PFA).

[0012] The porogen in step S1 is polyvinyl alcohol powder.

[0013] The stirring speed in step S1 is 240-300 r / min, the ultrasonic frequency of ultrasonic welding is 15-18 kHz, and the ultrasonic welding time is 0.5-1.2 s.

[0014] The inorganic particles described in step S1 are one of silicon dioxide, graphene oxide, titanium dioxide and cobalt dioxide, wherein the silicon dioxide is hydrophobic fumed silica nanoparticles, and the particle size of the silicon dioxide is 300 nm.

[0015] The mesh number of the stainless steel mesh in step S2 is 1500-3000 mesh.

[0016] In step S2, the stainless steel mesh needs to be pretreated before being laid flat on the automatic coating machine. The pretreatment method is: the stainless steel mesh is sequentially placed in acetone solution, anhydrous ethanol solution and deionized water for immersion and ultrasonic cleaning for 20 to 30 minutes, and then dried at 60 to 80° C. for 5-6 minutes after ultrasonic cleaning.

[0017] The thickness of the perfluoropolymer film layer in step S2 is 50-200 μm.

[0018] The rate of the gradient heating in step S3 is 5-10°C / min.

[0019] The perfluoropolymer tubular membrane obtained by the above preparation method.

[0020] The perfluoropolymer tubular membrane comprises an outer stainless steel mesh and an inner perfluoropolymer membrane layer. The oil flux of the perfluoropolymer tubular membrane at 90° C. and 0.08 MPa is 65.48-674.56 L·m -2 ·h -1 The oil flux at 120℃ and 0.08MPa is 72.73-987.59L·m -2 ·h -1 The oil flux at 150℃ and 0.08MPa is 77.25-1185.13L·m -2 ·h -1 ; Its static water contact angle is 100-145°, and after 20 mechanical durability tests, its static water contact angle is 95-120°.

[0021] The invention uses a stainless steel mesh as a substrate and a temperature-resistant and chemical-resistant perfluoropolymer as a membrane-forming material to develop an oil-water separation membrane for industrial waste oil treatment.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The perfluoropolymer selected in the present invention has excellent properties of heat resistance and corrosion resistance. Polyvinyl alcohol (PVA) powder is selected to act as a porogen and adhesive. Water is used as a solvent and inorganic particles are combined. The inorganic particles are used to construct a rough structure on the membrane surface and improve the hydrophobicity of the membrane. Through the interaction between the perfluoropolymer and the inorganic particles, the prepared perfluoropolymer tubular membrane is not only resistant to high temperatures, but also has the characteristics of being porous and high-flux, thereby improving the hydrophobicity, oil flux, service life and anti-pollution ability of the tubular membrane;

[0024] 2. The preparation process of the present invention is simple and easy to operate, and no organic solvent is used in the preparation process, and no harmful by-products are produced after the preparation. The method has low energy consumption, is green and environmentally friendly, and is conducive to industrial promotion and application;

[0025] 3. The present invention regulates the microstructure of the surface of the perfluoropolymer tubular membrane by regulating the content of inorganic particles, which makes it easy to prepare a porous membrane structure, thereby improving the operating efficiency of the tubular membrane in oil-water separation. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a schematic diagram of the planar enlarged structure of a 1500-mesh stainless steel mesh used in Example 1 of the present invention;

[0027] Figure 2 This is a high-power electron microscope image of the surface morphology of the perfluoropolymer tubular membrane prepared in Example 1 of the present invention;

[0028] Figure 3 This is a low-magnification electron microscopic image of the surface morphology of the perfluoropolymer tubular membrane prepared in Example 1 of the present invention;

[0029] Figure 4 This is a mapping diagram of the perfluoropolymer tubular membrane prepared in Example 1 of the present invention;

[0030] Figure 5 This is an electron microscope image of the permeation morphology of the casting solution of the perfluoropolymer tubular membrane prepared in Example 1 of the present invention;

[0031] Figure 6 This is an electron microscope image of the cross-sectional morphology of the perfluoropolymer tubular membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0033] In the following embodiments, the automatic coating machine was purchased from Yunfan (Tianjin) Instrument Co., Ltd., model Y01-VH; the film scraper was purchased from Yunfan (Tianjin) Instrument Co., Ltd., model SZQ four-sided preparation device (50-100-150-200 μm); the ultrasonic welding machine was purchased from Guangdong Linqi Ultrasonic Co., Ltd., model Dream S.

[0034] Fluorinated ethylene propylene (FEP) emulsion was purchased from Dongguan Xingwang Plastic Raw Materials Co., Ltd. with a solid content of 70wt%; polyvinylidene fluoride emulsion was purchased from Xutai Technology New Materials with a solid content of 60wt%; polytetrafluoroethylene emulsion was purchased from Zhengzhou Jinghong Battery Materials Co., Ltd. with a solid content of 60wt%; poly(tetrafluoroethylene perfluoroalkoxy vinyl ether) copolymer emulsion was purchased from Xutai Technology New Materials with a solid content of 60wt%.

[0035] Example 1

[0036] A method for preparing a perfluoropolymer tubular membrane comprises the following steps:

[0037] S1, preparation of casting solution: disperse poly(perfluoroethylene propylene) (FEP) emulsion (the solid content of FEP in the emulsion is 70wt%) and poly(vinyl alcohol) powder in deionized water, heat and stir at 300r / min in a 90°C water bath for 2h to obtain casting solution; keep stirring condition unchanged, weigh fumed silica nanoparticles and disperse them in the casting solution, continue stirring for 3h, then degas in a vacuum oven for 3h, and finally ultrasonically treat for 30min to obtain a uniform casting solution, in which the solid content of porogen (poly(vinyl alcohol) powder) is 6wt%, the solid content of inorganic particles (fumed silica nanoparticles) is 2wt%, and the solid content of perfluoropolymer (perfluoroethylene propylene, FEP) is 15wt%;

[0038] S2, preparation of nascent perfluoropolymer tubular membrane: select 1500 mesh stainless steel mesh as substrate, soak it in acetone solution, anhydrous ethanol solution and deionized water in turn and ultrasonically treat it for 20 minutes, remove surface impurities, place it in a vacuum hot air oven at 60°C and dry it for 6 minutes, spread the dried stainless steel mesh on an automatic coating machine, take 10 ml of casting liquid and place it on one end of the stainless steel mesh, and push the film scraper at a constant speed of 35 mm / s to obtain a perfluoropolymer film layer uniformly coated on the inner surface of the stainless steel mesh, then place it in a vacuum hot air oven at 80°C and dry it for 80 seconds to make the casting liquid initially solidify in hot air, and finally perform ultrasonic welding in an ultrasonic welding machine, with an ultrasonic frequency of 15 kHz and a time of 1.2 seconds to obtain a nascent perfluoropolymer tubular membrane;

[0039] S3, preparation of perfluoropolymer tubular membrane: placing the primary perfluoropolymer tubular membrane obtained in step S2 into a muffle furnace, heating it to 310°C at a sintering rate of 5°C / min, sintering it at this temperature for 5 minutes, and then cooling it naturally to obtain a high temperature resistant and corrosion resistant perfluoropolymer tubular membrane.

[0040] The surface morphology of the perfluoropolymer tubular membrane prepared in Example 1 was scanned by electron microscope, and the results were as follows: Figure 1-5 As shown, Figure 2 and 3 As shown ( Figure 2 yes Figure 3 The same position of the enlarged image), the inner surface of the perfluoropolymer tubular membrane can be observed to have a porous structure, such as Figure 5 As shown in the figure, part of the casting liquid can be observed on the outer surface of the perfluoropolymer tubular membrane, but no complete perfluoropolymer membrane layer is formed, indicating that the casting liquid can penetrate the inner surface of the stainless steel mesh and the outer layer during the preparation of the perfluoropolymer tubular membrane, showing that the coating of the stainless steel mesh is very sufficient. Figure 4 The aggregation state of inorganic particles on the surface of the perfluoropolymer tubular membrane can be observed. Figure 6This is a cross-sectional electron microscope image of the membrane, from which it can be observed that the interface bonding strength between the perfluoropolymer membrane layer and the stainless steel mesh is very strong.

[0041] The oil flux of the perfluoropolymer tubular membrane prepared in Example 1 was 674.56 L·m at a temperature of 90°C. -2 ·h -1 (0.08MPa), at 120℃ it is 987.59L·m -2 ·h -1 (0.08MPa), and 1185.13L·m at a high temperature of 150°C -2 ·h -1 (0.08MPa); its static water contact angle is 145°, and after 20 mechanical durability tests, the static water contact angle is 120°.

[0042] Example 2

[0043] A method for preparing a perfluoropolymer tubular membrane comprises the following steps:

[0044] S1, preparation of casting solution: weigh polyvinylidene fluoride (PVDF) emulsion (solid content of PVDF in the emulsion is 60%) and polyvinyl alcohol powder, mix and disperse in deionized water, heat and stir at 260r / min in a water bath at 80°C for 2h to obtain casting solution; keep stirring condition unchanged, weigh graphene oxide (powder) and disperse in the casting solution, continue stirring for 4h, then degas in a vacuum oven for 4h, and finally ultrasonically treat for 35min to obtain a uniform casting solution, in which the solid content of the porogen is 4wt%, the solid content of the inorganic particles (graphene oxide) is 2.5wt%, and the solid content of the perfluoropolymer (polyvinylidene fluoride, PVDF) is 15wt%;

[0045] S2, preparation of nascent perfluoropolymer tubular membrane: select 2000 mesh stainless steel mesh as substrate, immerse it in acetone solution, anhydrous ethanol solution and deionized water in turn and ultrasonically treat it for 25 minutes, remove surface impurities, place it in a vacuum hot air oven at 70°C and dry it for 5 minutes, spread the dried stainless steel mesh on an automatic coating machine, take 8 ml of casting liquid and place it on one end of the stainless steel mesh, and push the film scraper at a constant speed of 40 mm / s to obtain a perfluoropolymer film layer uniformly coated on the inner surface of the stainless steel mesh, then place it in a vacuum hot air oven at 60°C and dry it for 2 minutes to make the casting liquid initially solidify in hot air, and finally perform ultrasonic welding in an ultrasonic welding machine at an ultrasonic frequency of 16 kHz and a time of 1 second to obtain a nascent perfluoropolymer tubular membrane;

[0046] S3, preparation of perfluoropolymer tubular membrane: placing the primary perfluoropolymer tubular membrane obtained in step S2 into a muffle furnace, heating it to 320°C at a sintering rate of 6°C / min, sintering it at this temperature for 6 minutes, and then cooling it naturally to obtain a high temperature resistant and corrosion resistant perfluoropolymer tubular membrane.

[0047] The oil flux of the perfluoropolymer tubular membrane prepared in Example 2 was 481.24 L·m at a temperature of 90°C. -2 ·h -1 (0.08MPa), 521.37L·m at 120℃ -2 ·h -1 (0.08MPa), and 694.37L·m at a high temperature of 150°C -2 ·h -1 (0.08MPa); its static water contact angle is 121°, and after 20 mechanical durability tests, the static water contact angle is 110°.

[0048] Example 3

[0049] A method for preparing a perfluoropolymer tubular membrane comprises the following steps:

[0050] S1, preparation of casting solution: weigh polytetrafluoroethylene (PTFE) emulsion (solid content of PTFE in the emulsion is 60%) and polyvinyl alcohol powder, mix and disperse in deionized water, heat and stir in a water bath at 60°C for 5 hours, and the stirring speed is 280r / min to obtain casting solution; keep the stirring condition unchanged, weigh titanium dioxide (powder) and disperse in the casting solution, continue stirring for 5 hours, then degas in a vacuum oven for 4 hours, and finally ultrasonically treat for 40 minutes to obtain a uniform casting solution, in which the solid content of the porogen is 8wt%, the solid content of the inorganic particles (titanium dioxide) is 3wt%, and the solid content of the perfluoropolymer (polytetrafluoroethylene, PTFE) is 15wt%;

[0051] S2, preparation of nascent perfluoropolymer tubular membrane: select 2500 mesh stainless steel mesh as substrate, immerse it in acetone solution, anhydrous ethanol solution and deionized water in turn and ultrasonically treat it for 30 minutes, remove surface impurities, place it in a vacuum hot air oven at 75°C and dry it for 6 minutes, spread the dried stainless steel mesh on an automatic coating machine, take 12 ml of casting liquid and place it on one end of the stainless steel mesh, and push the film scraper at a constant speed of 38 mm / s to obtain a perfluoropolymer film layer uniformly coated on the inner surface of the stainless steel mesh, then place it in a vacuum hot air oven at 80°C and dry it for 100 seconds to make the casting liquid initially solidify in hot air, and finally perform ultrasonic welding in an ultrasonic welding machine, with an ultrasonic frequency of 17 kHz and a time of 0.8 seconds to obtain a nascent perfluoropolymer tubular membrane;

[0052] S3, preparation of perfluoropolymer tubular membrane: placing the primary perfluoropolymer tubular membrane obtained in step S2 into a muffle furnace, heating it to 330°C at a sintering rate of 8°C / min, sintering it at this temperature for 8 minutes, and then cooling it naturally to obtain a high temperature resistant and corrosion resistant perfluoropolymer tubular membrane.

[0053] The oil flux of the perfluoropolymer tubular membrane prepared in Example 3 was 435.17 L·m at a temperature of 90°C. -2 ·h -1 (0.08MPa), 476.98L·m at 120℃ -2 ·h -1 (0.08MPa), 537.16L·m at a high temperature of 150℃ -2 ·h -1 (0.08MPa); its static water contact angle is 118°, and after 20 mechanical durability tests, the static water contact angle is 105°.

[0054] Example 4

[0055] A method for preparing a perfluoropolymer tubular membrane comprises the following steps:

[0056] S1, preparation of casting solution: weigh poly(tetrafluoroethylene perfluoroalkoxy vinyl ether) copolymer (PFA) emulsion (solid content of PFA in the emulsion is 60%) and polyvinyl alcohol powder, mix and disperse in deionized water, heat and stir in a 90°C water bath for 2.5h, and the stirring speed is 300r / min to obtain casting solution; keep the stirring condition unchanged, weigh cobalt dioxide (powder) and disperse in the casting solution, continue stirring for 2h, then degas in a vacuum oven for 3h, and finally ultrasonically treat for 35min to obtain a uniform casting solution, in which the solid content of the porogen is 10wt%, the solid content of the inorganic particles (cobalt dioxide) is 2wt%, and the solid content of the perfluoropolymer (poly(tetrafluoroethylene perfluoroalkoxy vinyl ether) copolymer, PFA) is 15wt%;

[0057] S2, preparation of nascent perfluoropolymer tubular membrane: select 3000 mesh stainless steel mesh as substrate, immerse it in acetone solution, anhydrous ethanol solution and deionized water in turn and ultrasonically treat it for 25 minutes, remove surface impurities, place it in a vacuum hot air oven at 90°C and dry it for 6 minutes, spread the dried stainless steel mesh on an automatic coating machine, take 15 ml of casting liquid and place it on one end of the stainless steel mesh, and push the film scraper at a constant speed of 45 mm / s to obtain a perfluoropolymer film layer uniformly coated on the inner surface of the stainless steel mesh, then place it in a vacuum hot air oven at 90°C and dry it for 2 minutes to make the casting liquid initially solidify in hot air, and finally perform ultrasonic welding in an ultrasonic welding machine, with an ultrasonic frequency of 18 kHz and a time of 0.5 s to obtain a nascent perfluoropolymer tubular membrane;

[0058] S3, preparation of perfluoropolymer tubular membrane: placing the primary perfluoropolymer tubular membrane obtained in step S2 into a muffle furnace, heating it to 350°C at a sintering rate of 10°C / min, sintering it at this temperature for 10 minutes, and then cooling it naturally to obtain a high temperature resistant and corrosion resistant perfluoropolymer tubular membrane.

[0059] The oil flux of the perfluoropolymer tubular membrane prepared in Example 4 was 537.68 L·m at a temperature of 90°C. -2 ·h -1 (0.08MPa), 732.11L·m at 120℃ -2 ·h -1 (0.08MPa), 965.31L·m at a high temperature of 150℃ -2 ·h -1 (0.08MPa); its static water contact angle is 134°, and after 20 mechanical durability tests, the static water contact angle is 118°.

Claims

1. A method for preparing a perfluoropolymer tubular membrane, characterized in that: The following steps are involved: S1, preparation of casting solution: dispersing a liquid containing a perfluoropolymer and a porogen in deionized water, heating and stirring at 60-90°C for 2-5 hours to obtain a casting stock solution; keeping the stirring conditions unchanged, weighing inorganic particles and dispersing them in the casting stock solution, continuing to stir for 2-5 hours, and then vacuum degassing for 2-4 hours, and finally ultrasonically treating for 30-40 minutes to obtain a uniform casting solution, in which the solid content of the porogen is 4-10wt%, the solid content of the inorganic particles is 1-3wt%, and the solid content of the perfluoropolymer is 15wt%; S2, preparation of nascent perfluoropolymer tubular membrane: a stainless steel mesh is laid flat on an automatic coating machine, 8-15 ml of casting liquid is placed on one end of the stainless steel mesh, and a film scraper is uniformly advanced at a speed of 35-45 mm / s to obtain a perfluoropolymer film layer uniformly coated on the inner surface of the stainless steel mesh, followed by drying at 60-90° C. for 1-2 min to allow the casting liquid to initially solidify in hot air, and finally ultrasonically welded in an ultrasonic welding machine to obtain a nascent perfluoropolymer tubular membrane; S3, preparation of perfluoropolymer tubular membrane: placing the primary perfluoropolymer tubular membrane obtained in step S2 into a muffle furnace, gradually heating to 300-350° C. and sintering at 300-350° C. for 5-10 min, and obtaining a perfluoropolymer tubular membrane after natural cooling.

2. The preparation method according to claim 1, characterized in that: The perfluoropolymer is one of polyperfluoroethylene propylene, polyvinylidene fluoride, polytetrafluoroethylene, and poly(tetrafluoroethylene perfluoroalkoxy vinyl ether) copolymer; and the porogen in step S1 is polyvinyl alcohol powder.

3. The preparation method according to claim 1, characterized in that: The inorganic particles described in step S1 are one of silicon dioxide, graphene oxide, titanium dioxide and cobalt dioxide, wherein the silicon dioxide is hydrophobic fumed silica nanoparticles, and the particle size of the silicon dioxide is 300 nm.

4. The preparation method according to claim 1, characterized in that: The mesh number of the stainless steel mesh in step S2 is 1500-3000 mesh.

5. The preparation method according to claim 1, characterized in that: The thickness of the perfluoropolymer film layer in step S2 is 50-200 μm.

6. The preparation method according to claim 4, characterized in that: The stainless steel mesh needs to be pretreated before being laid flat on the automatic coating machine. The pretreatment method is: the stainless steel mesh is sequentially placed in acetone solution, anhydrous ethanol solution and deionized water for immersion and ultrasonic cleaning for 20 to 30 minutes, and then dried at 60 to 80° C. for 5 to 6 minutes.

7. The preparation method according to claim 1, characterized in that: The stirring speed in step S1 is 240-300 r / min; the ultrasonic frequency of ultrasonic welding in step S2 is 15-18 kHz, and the ultrasonic welding time is 0.5-1.2 s.

8. The preparation method according to claim 1, characterized in that: The rate of the gradient heating in step S3 is 5-10°C / min.

9. A perfluoropolymer tubular membrane prepared according to the preparation method according to any one of claims 1 to 8.

10. The perfluoropolymer tubular membrane according to claim 9, characterized in that The invention comprises an outer stainless steel mesh and an inner perfluoropolymer membrane layer, wherein the oil flux of the perfluoropolymer tubular membrane at 90°C and 0.08MPa is 65.48-674.56L·m -2 ·h -1 The oil flux at 120℃ and 0.08MPa is 72.73-987.59L·m -2 ·h -1 The oil flux at 150℃ and 0.08MPa is 77.25-1185.13L·m -2 ·h -1 ; Its static water contact angle is 100-145°, and after 20 mechanical durability tests, its static water contact angle is 95-120°.

Citation Information

Patent Citations

  • Enhanced type oil-absorbing film material, and assembly and preparation method thereof

    CN105597712A

  • Acid-base-resistant and high-temperature-resistant PASS / PP high-flux tubular ultrafiltration membrane

    CN113426308A

  • Polyvinylidene fluoride-based membrane, polyvinylidene fluoride composite nanofiltration membrane and preparation method of polyvinylidene fluoride-based membrane and polyvinylidene fluoride composite nanofiltration membrane

    CN114632428A

  • Small-aperture enhanced fluorinated ethylene propylene separation membrane and preparation method thereof

    CN117679973A

  • Tubular membrane continuous production device

    CN212142157U